2017
DOI: 10.1038/ncomms14755
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive population-wide analysis of Lynch syndrome in Iceland reveals founder mutations in MSH6 and PMS2

Abstract: Lynch syndrome, caused by germline mutations in the mismatch repair genes, is associated with increased cancer risk. Here using a large whole-genome sequencing data bank, cancer registry and colorectal tumour bank we determine the prevalence of Lynch syndrome, associated cancer risks and pathogenicity of several variants in the Icelandic population. We use colorectal cancer samples from 1,182 patients diagnosed between 2000–2009. One-hundred and thirty-two (11.2%) tumours are mismatch repair deficient per immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
88
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 35 publications
4
88
0
2
Order By: Relevance
“…Population‐based data from Iceland, for example, have shown that the country's overall prevalence of Lynch syndrome is approximately 0.442% (1:226), with the sizeable majority of cases being traced to 3 founder mutations: MSH6 p.L585P (estimated carrier frequency 0.080% or 1:1250), PMS2 p.M1? (0.092%; 1:1087), and PMS2 p.P246Cfs*3 (0.234%; 1:427) . Other research has demonstrated that the MSH6 p.Q4* founder mutation is particularly prevalent in French Canadian individuals, with an estimated carrier frequency of 0.249% (1:402), and haplotype analysis suggests that the mutation arose in a common ancestor from 430 to 656 years ago .…”
Section: Epidemiology Of Lynch Syndromementioning
confidence: 97%
“…Population‐based data from Iceland, for example, have shown that the country's overall prevalence of Lynch syndrome is approximately 0.442% (1:226), with the sizeable majority of cases being traced to 3 founder mutations: MSH6 p.L585P (estimated carrier frequency 0.080% or 1:1250), PMS2 p.M1? (0.092%; 1:1087), and PMS2 p.P246Cfs*3 (0.234%; 1:427) . Other research has demonstrated that the MSH6 p.Q4* founder mutation is particularly prevalent in French Canadian individuals, with an estimated carrier frequency of 0.249% (1:402), and haplotype analysis suggests that the mutation arose in a common ancestor from 430 to 656 years ago .…”
Section: Epidemiology Of Lynch Syndromementioning
confidence: 97%
“…Recent molecular advances have made it possible to distinguish another group of MSI‐H cancers designated as Lynch‐like syndrome (LLS) . Neither MLH1 promoter methylation nor germline mutations (LS) explain LLS tumors; instead, two somatic mutational events inactivating a given MMR gene are detectable in more than half of LLS tumors . Apart from MMR genes, the broader somatic mutational profiles of LLS tumors are unknown and only limited information is available of the clinicopathological characteristics and the incidence of LLS in the population …”
Section: Introductionmentioning
confidence: 99%
“…These cancers include colorectal, endometrial, ovarian, urothelial, small intestine, stomach, hepatobiliary, brain, and sebaceous cancers (Win et al, ). Prevalence of LS in the general population also varies, but it has been estimated that 1/200–1/400 individuals may carry a germline MMR pathogenic variant (Chen et al, ; Haraldsdottir et al, ). Identifying indviduals with LS to implement cancer surveillance such as routine colonoscopy and opportunities for preventative surgery, including prophylactic hysterectomy and bilateral salpingoophorectomy, is important (Gupta et al, ).…”
Section: Introductionmentioning
confidence: 99%